Zambia: Governance and Natural Resources - Werner, Karolina (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2016)
This paper analyzes the natural resources governance framework in Zambia. The research is the result of a broader project on natural resource governance with interviews performed in a number of countries in sub-Saharan Africa. The goal of the paper is to identify the gaps and inconsistencies within the Zambian natural resource policy framework, in an effort to broaden the understanding of how governance of the sector may be streamlined and optimized. It further offers suggestions on how other sectors, such as education, may be central to the development of a more successful natural resource framework. The paper focuses on Zambia as a country with a long history of mining and a relatively stable political environment, yet one in which tensions between government and the private sector remain, and policies on natural resource extraction which have been particularly volatile in recent years.